Consequences of Multiple Paternity for Female Fitness in an Ontario Population of Northern Map Turtles, 'Graptemys geographica' - Banger, Nicola A. (Université d'Ottawa / University of Ottawa, 2012)
Although sexual stereotypes paint males as being promiscuous and females as being choosy in order to increase their reproductive success, multiple mating by females is widespread and females of many taxa often produce progeny sired by multiple males – but why? In species in which there are no direct benefits associated with mating, females may adopt promiscuous mating strategies to increase their fitness through the acquisition of genetic benefits. Here, I examine the genetic mating system of map turtles, Graptemys geographica in Lake Opinicon. Based on the most conservative estimate, at least 71% of clutches in this population are sired by multiple males. There did not appear to be any relationship between female body size and frequency of multiple paternity. There was a marginally significant effect of multiple paternity on hatching success and survival of clutches, but there was no effect on hatchling morphology or locomotor performance.
Keywords: polyandry; multiple paternity; turtle; hatchling; genetic benefits